Implementasi Sharenting Di Media Sosial Sebagai Penggeser Dokumentasi Tumbuh Kembang Anak Dari Analog Ke Digital - Gunawan, Muchamad Ganda (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2023)
The purpose of this study is to examine the reasons parents choose social media as a sharenting medium and medium for digital documentation of children's growth and development. How is the topic of sharenting seen in the perspective of communication, technology, industry, society and the future. This research approach is qualitative. The data collection method was carried out by interviewing parents who have children aged 0-19 years and actively using social media platforms, and doing sharenting in their accounts virtually. The results show that social media has the advantage of doing sharenting and as a digital documentation medium compared to analog or conventional methods. The conclusion is documentation of child growth and development has shifted from physical to digital media due to technological developments, on consideration of storage memory capacity, ease of access, ability to maintain the quality of stored photos and videos, also as the main function of social media, which is to share.